2020
DOI: 10.3390/ani10122196
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte Selection for In Vitro Embryo Production in Bovine Species: Noninvasive Approaches for New Challenges of Oocyte Competence

Abstract: The efficiency of producing embryos using in vitro technologies in livestock species rarely exceeds the 30–40% threshold, indicating that the proportion of oocytes that fail to develop after in vitro fertilization and culture is considerably large. Considering that the intrinsic quality of the oocyte is one of the main factors affecting blastocyst yield, the precise identification of noninvasive cellular or molecular markers that predict oocyte competence is of major interest to research and practical applicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 174 publications
(224 reference statements)
1
19
0
4
Order By: Relevance
“…Besides, previous studies in other species showed that forskolin and IBMXs’ beneficial effects on embryo development are also related to an increased ATP, and oxygen consumption [ 22 , 46 ], modulation of lipid content [ 19 ], and reduced spindle abnormalities [ 22 ], amongst others. Along with DNA integrity, these parameters have often been regarded as good indicators of oocyte quality [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, previous studies in other species showed that forskolin and IBMXs’ beneficial effects on embryo development are also related to an increased ATP, and oxygen consumption [ 22 , 46 ], modulation of lipid content [ 19 ], and reduced spindle abnormalities [ 22 ], amongst others. Along with DNA integrity, these parameters have often been regarded as good indicators of oocyte quality [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The developmental capacity of reconstructed embryos is influenced by the intrinsic quality of oocytes [ 34 ]. Proper nuclear and cytoplasmic maturation is the key element of a good quality oocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Как известно, эффективность IVP технологии определяется не только качеством исходной популяции гамет, выделенных из яичников животных (8,9), но и условиями среды, окружающей ооциты in vitro (10,11). Наиболее важный этап культивирования -это созревание ооцитов.…”
unclassified
“…Результаты. К настоящему времени достигнут существенный прогресс в разработке IVP технологии у крупного рогатого скота с использованием донорских ооцитов, однако полноценность эмбрионов, развившихся in vitro из OPU-ооцитов, по-прежнему остается значительно более низкой, чем развившихся in vivo (5)(6)(7)(8). Идентификация биологически уместных факторов, отвечающих за регуляцию качества ооцитов в период их созревания in vitro, будет способствовать решению этой проблемы (12)(13)16).…”
unclassified